Influence of SARS-CoV2 Pandemic on Colorectal Cancer Diagnosis, Presentation, and Surgical Management in a Tertiary Center: A Retrospective Study - Roman Taulean; Roxana Zaharie; Dan Valean; Lia Usatiuc; Mohammad Dib; Emil Moiș; Calin Popa; Andra Ciocan; Alin Fetti; Nadim Al-Hajjar; Florin Zaharie (Diagnostics)
Background: Oncological surgery during the COVID-19 pandemic was performed only in carefully selected cases, due to variation in the allocation of resources. The purpose of this study was to highlight the impact of the pandemic lockdown on the presentation, diagnosis, and surgical management of colorectal cancers as well as the post-pandemic changes in this area. Material and methods: This single center, retrospective comparative study contained 1687 patients, divided into three groups with equal time frames of two years, consisting of a pre-pandemic, pandemic, and post-pandemic period, in which preoperative and perioperative as well as postoperative parameters were compared. Results: Statistically significant differences regarding environment, type of admission, and ASA score, as well as a more advanced tumoral stage, increased number of important postoperative complications, and a lower minimally invasive surgical approach, were highlighted within the pandemic group. Statistically significant differences regarding emergency diagnosis as well as late diagnosis were highlighted. There were no significant differences regarding the tumor location, postoperative 30-day mortality, or hospitalization duration. Conclusions: COVID-19 significantly impacted the surgical timing in colorectal cancer, as well as addressability for the rural population, with a marked decrease in elective cases as well as an increased number of cases diagnosed in an emergency setting, with locally advanced tumors. However, no significant changes in postoperative mortality or hospitalization duration were highlighted. In addition, most of the changes highlighted were reverted in the post-pandemic period. Further studies are required to observe the long-term effects in terms of morbidity and mortality, regarding the delay of diagnosis and oncological treatment.